MACHISMO IN THE DOCK – A CRITICAL FEMINIST ANALYSIS OF BRAZILIAN CRIMINAL POLICY CONCERNING THE COMBAT OF VIOLENCE AGAINST WOMEN - Lucchesi, Guilherme Brenner (2015)
O presente artigo tem por objetivo realizar uma análise crítica dos discursos feministas, que levaram recentemente à promulgação das leis brasileiras responsáveis por tornar mais severa a punição da violência contra a mulher, de modo a demonstrar como não conseguem escapar das armadilhas cognitivas estabelecidas pela dominação masculina naturalizada nas sociedades ocidentais e como têm servido ao desenvolvimento de uma biopolítica neoliberal.The aim of this article is to critically analyze the feminist discourse that led to the recent enactment of Brazilian laws that increased the penalties for violence against women, in order to demonstrate that they cannot escape the cognitive traps established by male domination naturalized in Western societies and how they have served the development of neoliberal biopolitics